2006
DOI: 10.1158/0008-5472.can-05-4233
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of a Novel Intradermal Idiotype Vaccine in Patients with Advanced B-Cell Lymphoma: Specific Immune Responses Despite Profound Immunosuppression

Abstract: The immunoglobulin receptor of B-cell lymphomas constitutes a specific tumor antigen (idiotype) and a target for active immunotherapy. Encouraging results have been reported in phase II trials after s.c. vaccination of follicular lymphoma patients during clinical remission with idiotype produced from eukaryotic cell lines and coupled to an immunogenic carrier macromolecule. We have developed a good manufacturing protocol for rapid expression of idiotype vaccines as recombinant Fab fragments in Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…9 Peptide mapping experiments revealed that these T-cell responses are consistently directed against human leukocyte antigen (HLA) class I-restricted peptides from the complementarity-determining regions (CDRs) or against hypermutated idiotype epitopes. 8,9 These findings are in accordance with animal studies demonstrating T-cell tolerance for germlineencoded immunoglobulin sequences but responsiveness to novel idiotopes arising from junctional diversity or somatic mutations. 10 Because mouse models have also shown T cell-mediated immunosurveillance against hypervariable idiotypic peptides, 11 we sought to obtain evidence that spontaneous idiotype-directed T-cell immunity is operational in nonimmunized lymphoma patients and impairs expansion of malignant B-cell clones that express an idiotype with high immunogenicity.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…9 Peptide mapping experiments revealed that these T-cell responses are consistently directed against human leukocyte antigen (HLA) class I-restricted peptides from the complementarity-determining regions (CDRs) or against hypermutated idiotype epitopes. 8,9 These findings are in accordance with animal studies demonstrating T-cell tolerance for germlineencoded immunoglobulin sequences but responsiveness to novel idiotopes arising from junctional diversity or somatic mutations. 10 Because mouse models have also shown T cell-mediated immunosurveillance against hypervariable idiotypic peptides, 11 we sought to obtain evidence that spontaneous idiotype-directed T-cell immunity is operational in nonimmunized lymphoma patients and impairs expansion of malignant B-cell clones that express an idiotype with high immunogenicity.…”
Section: Introductionsupporting
confidence: 83%
“…Most of these bona fide peptides are expected to physically bind to HLA and to serve as functional T-cell epitopes. 8,9,[16][17][18] In a matched-pair comparison of the idiotype BIMAS sum scores, the V H region of an affected patient's own lymphoma had lower HLA-binding scores than allogeneic idiotypes (Figure 1). No such global difference was observed for idiotype V L regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphoma samples were obtained with written informed consent from the Freiburg University idiotype vaccination program [2][3][4] and the hematology biobank of Leiden University Medical Center with approval of the ethics committee of Freiburg University. HLA alleles were identified by serotyping and high-resolution genotyping (Olerup SSP kit, Qiagen, Hilden, Germany).…”
Section: Evidence For Idiotype-directed Immunosurveillance Is Restricmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Idiotype vaccines were shown to be safe and induced sustained antitumor antibody and CD4 Ï© and CD8 Ï© T-cell responses in patients with follicular lymphoma (FL), chronic lymphocytic leukemia (CLL), mantle cell lymphoma (MCL), and diffuse large B-cell lymphoma (DLBCL). [5][6][7][8][9][10][11] Furthermore, idiotype vaccines induced molecular remissions when administered after standard chemotherapy. 10 A recently completed randomized, double blind, multicenter phase 3 clinical trial showed that idiotype vaccination improves disease-free survival when administered in the setting of minimal residual disease in FL, providing proof of principle that therapeutic vaccines can improve clinical outcome in these patients.…”
Section: Introductionmentioning
confidence: 99%